1984
DOI: 10.1111/j.1464-5491.1984.tb01953.x
|View full text |Cite
|
Sign up to set email alerts
|

Seven Years Experience of Home Management in Pregnancy in Women with Insulin‐dependent Diabetes

Abstract: Fifty-eight of a consecutive series of 75 pregnancies in women with insulin-dependent diabetes went into the third trimester. Diabetes was managed by home blood glucose monitoring and women were not routinely admitted at any stage before delivery. The mean number of in-patient days before delivery was 15 for the whole series but has been reduced to 9 during the past four years. Each woman performed an average of 171 blood glucose measurements during her pregnancy. Mean blood glucose (including post-prandial le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

1986
1986
1992
1992

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 24 publications
3
3
0
Order By: Relevance
“…The incidence of neonatal complications was not much different between the two groups, and neither was the degree of m~ernal blood glucose control or evidence of fetal hyperinsulinism. This accords with the experience in Nottingham [24], where it was found that the~cost of mefErs and strips was repaid many times over in the saving of hospital costs, to say nothing of patient popularity.…”
Section: Internal Medical Aspectssupporting
confidence: 73%
See 1 more Smart Citation
“…The incidence of neonatal complications was not much different between the two groups, and neither was the degree of m~ernal blood glucose control or evidence of fetal hyperinsulinism. This accords with the experience in Nottingham [24], where it was found that the~cost of mefErs and strips was repaid many times over in the saving of hospital costs, to say nothing of patient popularity.…”
Section: Internal Medical Aspectssupporting
confidence: 73%
“…Other factors such as better nutrition, improved social circumstances, and recognition of the risks of smoking and of alcohol must play a part. Skyler [26] states dogmatically that the advent of patient self-monitoring of plasma glucose has made the desired metabolic normality feasible and practical, but Tattersall and his colleagues [24], during 7 years experience of home monitoring in diabetic pregnancy, were unable to prevent the occurrence of three serious congenital abnormalities in 58 pregnancies. They recognised that completely normal mean blood glucose levels were not achieved in any trimester or at any time of the day, but the mean haemoglobin A, did fall into their normal range (5.5-8.5%) in the second and third trimesters.…”
Section: Fetal Abnormalitiesmentioning
confidence: 99%
“…In our study, neonatal complications were uncommon and none was serious. The incidence of neonatal hypoglycaemia was 12%, which is similar to that in other series [9,15]. Interestingly, we have been able to confirm the finding of KNIGHT et al [12] that fetal macrosomia is not necessarily associated with poor diabetic control in the mothers.…”
Section: Discussionsupporting
confidence: 91%
“…The overall outcome of pregnancy in our series was good, with no significant maternal or fetal complications. Our overall Caesarean section rate was only 23%, which compares favourably with a rate of 66% in HELLER et al's series [9], although DRURY [7] did achieve a rate of only 20%. In our study, neonatal complications were uncommon and none was serious.…”
Section: Discussionsupporting
confidence: 55%
“…Despite attention to all these measures, macrosomia will still occur but should not be associated with significant perinatal complications if the patient has achieved good glycemic control in the latter half of pregnancy and if neonatal hypoglycemia is rapidly detected and corrected. Even if good glycemic control in pregnancy will not guarantee the birth of a nonmacrosomic infant, there is such compelling evidence that meticulous diabetic control reduces perinatal morbidity and mortality that euglycemia remains the therapeutic aim for every diabetic patient during pregnancy (8,19,(27)(28)(29)(30)(31).…”
Section: Resultsmentioning
confidence: 99%